2004
DOI: 10.1021/cm049794x
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity and Vapor-Sensing Properties of ω-(3-Thienyl)alkanethiol-Protected Gold Nanoparticle Films

Abstract: Gold nanoparticles protected with thiophene-terminated alkanethiols having different alkane chain lengths have been synthesized, and vapor-sensing properties of their spin-coated films have been investigated. Transmission electron microscopy and measurement of the sulfur and gold peak areas of the films by X-ray photoelectron spectroscopy indicate gold core diameters in the 3−5-nm range. Exposure of the films to chloroform, toluene, hexane, and ethanol vapors results in significant and selective increases in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 25 publications
1
74
0
Order By: Relevance
“…Thin films of such gold nanoparticle-organic hybrids can be used as chemiresistor sensors, whereby changes in the conductivity of the thin film can be observed in the presence of an analyte as a result of an increase in the nanoparticle separation due to swelling of the nanoparticle film [16][17][18][19][20][21]. Although the concept of using gold nanoparticles for chemical sensing is well established for vapor-phase sensing, we have recently demonstrated that hexanethiol-Au NP can be used as chemiresistors to determine the presence of organic molecules even in a highly concentrated salt solution (1 M KCl) [7] through appropriate design of the electrode geometry (electrode length and separation) and by the application of a low frequency (1 Hz) AC voltage.…”
Section: Introductionmentioning
confidence: 99%
“…Thin films of such gold nanoparticle-organic hybrids can be used as chemiresistor sensors, whereby changes in the conductivity of the thin film can be observed in the presence of an analyte as a result of an increase in the nanoparticle separation due to swelling of the nanoparticle film [16][17][18][19][20][21]. Although the concept of using gold nanoparticles for chemical sensing is well established for vapor-phase sensing, we have recently demonstrated that hexanethiol-Au NP can be used as chemiresistors to determine the presence of organic molecules even in a highly concentrated salt solution (1 M KCl) [7] through appropriate design of the electrode geometry (electrode length and separation) and by the application of a low frequency (1 Hz) AC voltage.…”
Section: Introductionmentioning
confidence: 99%
“…The current‐voltage ( I–V ) characteristics for the self‐assembled aggregates of 1 and 2 deposited on insulating glass substrates with ITO interdigitated electrodes (IDEs) are shown in Figure and summarized in Table . The devices made from two different kinds of aggregates exhibited similar conductive behavior, with the conductivity(σ) of about 1.1×10 −5 S cm −1 and 3.7×10 −5 S cm −1 in dry nitrogen (RH=0%) for the aggregates of 1 and 2 , respectively, Figure (solid lines). The higher conductivity of 2 with respect to that of 1 might be attributed to the higher ordered molecular arrangement due to the stronger π‐π interactions among the adjacent molecules in the aggregate of 2 as revealed by the UV‐vis, IR spectra and SEM experiments.…”
Section: Resultsmentioning
confidence: 99%
“…They have proposed a physical, rather than chemical, approach to the sensing of combustible odours. Inspired by Wohltjen and Snow, Ahn and co-workers [11] exposed films of -(3-thienyl)alkanethiol-gold core/shell nanoparticles to several combustible odours, and found an increase in resistance due to swelling of the films in the odour.…”
Section: Introductionmentioning
confidence: 99%
“…Such ligands are expected to be most compatible with similarly apolar alkane odours, but to reject more polar or hydrogen-bonding odours. Also, rather than spincasting [11], we processed core/shell nanoparticles by the Langmuir-Schäfer (LS) printing method [13]. The LS printing allows the formation of dense, highly ordered monolayer films on a water surface prior to transferring films to the solid substrate, while still avoiding the coalescence and fusing of neighbouring gold particles.…”
Section: Introductionmentioning
confidence: 99%